WHAT IS NEWTON’S LAW OF INERTIA?: THE USE OF QUESTIONS IN SCIENCE LECTURES - Akhyar Rido (Faculty of Languages and Arts, Universitas Negeri Yogyakarta, 2019)
An inability to recognize discourse structure is seen by applied linguists as one of the main problems of non-native speaker students in understanding science lectures in English. In this circumstance, the use of interactive discourse structure like questions is salient as it is likely to aid comprehension. This research investigated the use of questions in science lectures in English in a university in Malaysia. By using conversation analysis (CA), a science lecturer was selected, video-recorded, and interviewed during two formal teaching hours. The findings show that the lecturer used a large quantity of display and referential questions. Display questions, comprising questions with ‘do’, ‘have’ and to be ‘is’ and ‘are,’ were posed to encourage participation and check students’ understanding toward the materials at hand. Meanwhile, referential questions, mostly started with ‘what’ or ‘what do you think’, ‘how’, ‘when’ and ‘where’, were employed to guide the students to understand science concept and stimulate critical thinking skills. This research, thus, suggested science lecturers to use questions in various types and ways to foster learning.Keywords: questions, types, functions, science lecture APAKAH HUKUM INERSIA NEWTON?:PENGGUNAAN PERTANYAAN DALAM PERKULIAHAN SAINS AbstrakKetidakmampuan dalam mengenali struktur wacana dilihat oleh ahli linguistik terapan sebagai salah satu masalah utama mahasiswa bukan penutur asli dalam memahami perkuliahan sains dalam bahasa Inggris. Dalam keadaan ini, penggunaan struktur wacana interaktif seperti pertanyaan sangat penting karena akan membantu memahami perkuliahan. Penelitian ini mengkaji penggunaan pertanyaan dalam perkuliahan sains dalam bahasa Inggris di satu universitas di Malaysia. Dengan menggunakan analisis percakapan (CA), seorang dosen sains dipilih, direkam, dan diwawancara selama dua perkuliahan formal. Hasil penelitian menunjukkan bahwa dosen banyak menggunakan jenis pertanyaan display dan referensial. Pertanyaan display, yang terdiri dari pertanyaan dengan ‘do’, ‘have’, dan ‘is’ serta ‘are,’ berfungsi untuk mendorong partisipasi dan memeriksa pemahaman mahasiswa terhadap materi yang disampaikan. Sementara itu, pertanyaan referensial, dimulai dengan ‘what’ atau ‘what do you think’, ‘how’, ‘when’ dan ‘where’, digunakan untuk memandu mahasiswa memahami konsep sains dan merangsang keterampilan berpikir kritis. Oleh karena itu, hasil penelitian ini dapat menjadi pertimbangan para dosen sains untuk menggunakan berbagai jenis pertanyaan dengan berbagai cara untuk membantu memahami perkuliahan.Kata kunci: pertanyaan, jenis, fungsi, perkuliahan sains